Small Signal Stability Analysis of Kalimantan 500 KV Electricity System - Agus Sadid, Akbar Syahbani; Mutiarso, Ismayahya Ridhan; Arif, Fauzany; Muda, Kemal Iskandar; Prawira, Fadhil Bintang (Journal of Advanced Technology and Multidiscipline, 2023)
Small signal stability refers to the ability of a system to return to equilibrium after experiencing a small disturbance. In this research, the Kalimantan electricity system will be analyzed for the stability of its small signal. Analysis of the stability of small signals in electrical systems including local disturbances and inter-area disturbances. The Kalimantan system will be analyzed using Power Factory software. System analysis was carried out by evaluating the eigenvalues "‹"‹(real part and imaginary part), oscillation frequency (damped frequency and frequency ratio) produced in the Kalimantan 500 KV electricity analysis. In the analysis results, the Kalimantan system is categorized as stable as indicated by the real part and imaginary part values "‹"‹located on the negative side of the Cartesian coordinate curve. Then, analyzing small signals, there are 117 modes categorized as local mode and 4 modes categorized as inter area mode.